Yann Guy, L’impact de la finance de marché sur le comportement d’investissement des entreprises : une confrontation des approches microéconomique et macroéconomique - Yann Guy (Revue de la Régulation)
The research focuses on the links between the growth strategy of non-financial firms and the conditions of its financing in France since the early 1980s. According to this objective, the empirical work consists in making a comparison between the facts one observes at the microeconomic level on the basis of the large quoted groups’ consolidated accounts, and at the macroeconomic level on the basis of French national accounts. The thesis highlights two key points. Within the framework of finance-dominated accumulation regime and under the impulse of the large quoted groups, corporate investment (i) remains very low in the long term, with a significant worsening at the end of the period (ii) fluctuates according to a deflationary financial cycle. We test these conclusions through VECM modeling on national accounts data and through first-difference GMM estimates on a sample of French large companies which are quoted on the SBF 250 Index. The behavioral equations are issued from post-Keynesian SFC models.